The effect of polyunsaturated fatty acids on cholesterol metabolism - Pal, Sebely, 1965- (1991)
Thesis (M.Sc.)--Memorial University of Newfoundland, 1992. Biochemistry Bibliography: leaves 112-125. Atherosclerosis is characterized by deposition of cholesterol and esterified cholesterol in cells of the vascular intima. These lipid laden cells are called foam cells due to their microscopic appearance and arise primarily from smooth muscle cells and monocyte macrophages. It is believed that the transformation of these cells into foam cells is a key step in the initiation of atherosclerosis. Therefore, to better understand the process of atherogenesis it is important to investigate the mechanisms that may regulate cholesterol esterification and hence the formation of foam cells. -- Polyunsaturated fatty acids (PUFAs) in the diet can substantially reduce the incidence of coronary heart disease. However, dietary ω-3 polyunsaturated fatty acids found primarily in marine oils have been shown to be better in reducing the risk of atherosclerosis than other polyunsaturated fatty acids. Unfortunately, it is unclear how ω-3 PUFAs are involved in delaying the atherogenic process. It is possible that these fatty acids may be antiatherogenic by inhibiting cholesterol esterification or increasing cholesterol removal from cells thereby inhibiting the initial step of foam cell formation. -- The major objective of this study was to investigate the impact of different polyunsaturated fatty acid enrichment of nonhepatic tissues on cholesterol esterification and cholesterol efflux. Human fibroblasts and macrophages were enriched with either linoleic acid (18:3, ω-6) or eicosapentaenoic acid (20:5, ω-3) by supplementing the culture medium. The incorporation of radiolabelled oleoyl CoA into cholesterol esters was reduced by 44% when human fibroblasts were enriched with ω-3 polyunsaturated fatty acids compared with cells enriched with ω-6 polyunsaturated fatty acids. Also, macrophages enriched with ω-3 PUFAs had significantly lower (52%) total cholesterol content than those enriched with ω-6 PUFAs. Cholesterol efflux was measured in cells enriched with ω-3 PUFAs and ω-6 PUFAs. In the presence of HDL, the rate of efflux of radiolabelled cholesterol from cells enriched with ω-3 PUFAs was substantially faster (2x) than efflux from cells enriched with ω-6 PUFA enriched cells. The data suggests that ω-3 PUFAs may be antiatherogenic by inhibiting cholesterol esterification and by accelerating cholesterol efflux from nonhepatic cells.